2021
DOI: 10.3390/cancers13030501
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Reduction after Craniospinal Irradiation via Helical Tomotherapy in Patients with Medulloblastoma: A Unicentric Retrospective Analysis

Abstract: Objectives: Recent trials with craniospinal irradiation (CSI) via helical Tomotherapy (HT) demonstrated encouraging medulloblastoma results. In this study, we assess the toxicity profile of different radiation techniques and estimate survival rates. Materials and Methods: We reviewed the records of 46 patients who underwent irradiation for medulloblastoma between 1999 and 2019 (27 conventional radiotherapy technique (CRT) and 19 HT). Patient, tumor, and treatment characteristics, as well as treatment outcomes—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Based on our results, exceeded CSI 36 Gy, CSI high dose results the single risk factor for the develop of G1 and G2 permanent alopecia in the whole-scalp as well as in the PCF region, independent of other clinical and therapeutic variables (7,(19)(20)(21). Figure 1 shows the multivariate permanent hair loss etiopathogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…Based on our results, exceeded CSI 36 Gy, CSI high dose results the single risk factor for the develop of G1 and G2 permanent alopecia in the whole-scalp as well as in the PCF region, independent of other clinical and therapeutic variables (7,(19)(20)(21). Figure 1 shows the multivariate permanent hair loss etiopathogenesis.…”
Section: Discussionmentioning
confidence: 68%
“…This article, ranked 2nd in terms of total citations with a total of 279, and ranked 1st in terms of CPY with a score of 22.3, had important value in the dosimetry comparative study of prostate cancer. This study suggests that all other approaches yield treatment S2) Type of tumor head and neck cancer 15 (6,11,14,19,20,27,36,39,41,55,64,72,90,91,96) cancers with complex and large targets* 14 (3,9,16,17,35,54,57,62,74,78,88,95,98,99) breast cancer 12 (13, 18, 26, 32, 44, plans of improved quality when compared to 3D-CRT, with HT providing best OAR sparing and VMAT being the most efficient treatment option. This conclusion was supported by other highly cited articles (30)(31)(32).…”
Section: Prostate Cancermentioning
confidence: 86%
“…Cranial spinal irradiation is mainly indicated for patients diagnosed with CNS tumors, such as medulloblastoma ( 20 , 21 ), germinoma ( 22 ), etc., which is a typical case with complex and large targets and is one of the typical indications for HT. In comparison to other techniques, HT provides superior target coverage, ensuring that the radiation is delivered uniformly and consistently throughout the affected area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies analyzed the pulmonary toxicity in patients who received HT-CSI, one of which reported that none of 18 pediatric patients who received HT-CSI were diagnosed with symptomatic acute radiation pneumonitis 23 . Öztunali et al reported that 2 out of 43 patients aged 7 on average (range 1–56) who received HT-CSI for medulloblastoma were diagnosed with grade 1 pneumonitis and 1 was diagnosed with grade 3 pneumonitis 24 . As these studies showed, all pulmonary toxicity studies in patients who received CSI were mostly conducted on pediatric patients.…”
Section: Discussionmentioning
confidence: 99%